Interpretative transport modeling of the WEST boundary plasma: main plasma and light impurities. (30th October 2020) - Gallo, A.; Sepetys, A.; Marandet, Y.; Bufferand, H.; Ciraolo, G.; Fedorczak, N.; Brezinsek, S.; Bucalossi, J.; Coenen, J.; Clairet, F.; Corre, Y.; Desgranges, C.; et al.
Abstract: Understanding impurity transport in tokamak plasmas is crucial to control radiative losses and material migration in future magnetic fusion reactors. In this work we deploy the SolEdge2D-EIRENE code to model the boundary plasma in a WEST discharge, satisfactorily reproducing measurements of both upstream and divertor plasma conditions. The spatial distribution of oxygen, studied here as a representative light impurity, is compared to vacuum ultraviolet spectroscopy measurements acquired with an oscillating line of sight. The simulation captures a key feature of the experiment, namely a factor of ≃2 higher oxygen brightness in the inner divertor region compared to the outer one. This spatial asymmetry in oxygen concentration is interpreted by analyzing the balance of friction forces and thermal gradient forces that the light impurity exchanges with the main plasma.